ROLE OF CLEXANE TO IMPROVE AFI AFTER 28 WEEKS GESTATION - Dr Maniba Habib,Dr Nasreen Akhter, Dr Sara Akram,Dr Farzana Sabir,Dr. Huma Muneer ,Prof Dr.Shazia Saeed (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective: Oligohydramnios is when the AFI is less than or equal to 5 cm. Borderline AFI ranges from 5.1 cm to 8 cm. Incidence of borderline AFI compared to normal AFI (8.1–18 cm) varies from 6% to 44% as mentioned in the studies. Decreased amniotic fluid can cause severe consequences to both mother and the fetus.